(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
This paper elucidate the results of the research "Museological Digital Storytelling in the Social Communication of Science," which aimed to identify innovations in digital and transmedia narratives from the museums of Bogot D.C., Colombia. A systematic review methodology was employed, using web content analysis and netnography to collect both quantitative and qualitative data. The results obtained here enabled the identification of the current state of publications on transmedia narratives, science communication, and museology, as well as their implementation in museums from Bogot D.C. Colombia.